Rheumatoid Arthritis and Atherosclerosis : Revmatoidni artritis in ateroskleroza - Holc, Iztok; Pahor, Artur (Acta Medico-Biotechnica, 2021)
Life expectancy of rheumatoid arthritis (RA) patients can be reduced by 3–18 years. Cerebrovascular and cardiovascular events (myocardial infarction and stroke) as a consequence of accelerated atherosclerosis are the main cause of death in RA patients. Atherosclerosis is a widespread pathologic process in medium– to–large arteries responsible for cardiovascular diseases. Atherosclerosis shares many similarities in immune– pathophysiological mechanisms with autoimmune inflammatory diseases such as RA. Classical and non–classical risk factors are the cause for accelerated atherosclerosis in RA patients. Non–classical risk factors include some specific biochemical substances (homocysteine, cystatin C, lipoproteins) as well as inflammatory cytokines and adhesion molecules. For the diagnosis of accelerated atherosclerosis in RA patients, ultrasound of internal carotid arteries with measurement of intima media thickness can be employed. Here, we describe the practical factors involved in the diagnosis of accelerated atherosclerosis in RA patients.